The informative coverage of immigration on Televisión Española. The case of the Aquarius ship - Arévalo Salinas, Alex Iván; Najjar Trujillo, Tamer Al; Abib, Tayane Aidar [UNESP] (Universidad Complutense de Madrid (UCM), 2021)
This research compares the news coverage of La 1 (Televisión Española) during the arrival of the 626 people rescued by the Aquarius ship in the Mediterranean Sea in 2018 with other immigration issues, which were broadcast between June 17 and 23, 2018. The research uses content analysis to review five aspects: thematic analysis, duration, sources used, terminology and journalistic decisions. The results express that the coverage of Aquarius used an empowering discourse, different from the traditional coverage of other migratory events marked by the criminalization of these people. The scarce presence of migrants as news sources is also observed. The testimony is not worked in depth to know their personal stories, their motivations and wishes.
La cobertura informativa de la inmigración en Televisión Española. El caso del barco Aquarius
Keywords: Immigration; Information sources; Public television; Spanish television